2018
DOI: 10.1371/journal.pone.0191112
|View full text |Cite
|
Sign up to set email alerts
|

Association between PM10, PM2.5, NO2, O3 and self-reported diabetes in Italy: A cross-sectional, ecological study

Abstract: IntroductionAir pollution represents a serious threat to health on a global scale, being responsible for a large portion of the global burden of disease from environmental factors. Current evidence about the association between air pollution exposure and Diabetes Mellitus (DM) is still controversial. We aimed to evaluate the association between area-level ambient air pollution and self-reported DM in a large population sample in Italy.Materials and methodsWe extracted information about self-reported and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 48 publications
(56 reference statements)
5
16
0
1
Order By: Relevance
“…For example, epidemiological studies have shown that prenatal and childhood exposure to ambient or traffic-related air pollutants (TRAP) is associated with more rapid BMI increases during childhood, increased prevalence of obesity, and metabolic dysregulation 28 . In adults, similar associations have been reported with higher incidence of metabolic syndrome, insulin resistance, and diabetes 917 . Collectively, these observations suggest that exposure to ambient air pollution, including during critical periods of development, may contribute to obesity in early life and its metabolic consequences later in adulthood.…”
Section: Introductionsupporting
confidence: 73%
“…For example, epidemiological studies have shown that prenatal and childhood exposure to ambient or traffic-related air pollutants (TRAP) is associated with more rapid BMI increases during childhood, increased prevalence of obesity, and metabolic dysregulation 28 . In adults, similar associations have been reported with higher incidence of metabolic syndrome, insulin resistance, and diabetes 917 . Collectively, these observations suggest that exposure to ambient air pollution, including during critical periods of development, may contribute to obesity in early life and its metabolic consequences later in adulthood.…”
Section: Introductionsupporting
confidence: 73%
“…This study only made an analysis from the aspect of incidence prediction, and provided some reference for the optimal allocation of health resources in advance. Some studies had shown that many factors were related to the high incidence of diseases, such as socio-economic factors [34,35], demographic factors [36,37] meteorological factors [38][39][40][41], etc. The related research on the influencing factors of HB incidence should also be carried out in time, which can also help the prevention and control of HB.…”
Section: Plos Onementioning
confidence: 99%
“…Mehrere aktuelle Studien haben mit einem Querschnittdesign den Zusammenhang zwischen Luftverschmutzung und der Prävalenz des Typ 2-Diabetes untersucht und ebenfalls gemischte Ergebnisse beobachtet, mit positiven Zusammenhängen für Feinstaub, Stickoxide und Ozon in Italien [31], für Feinstaub und NO 2 in Nordamerika und in der Schweiz [17,32] [32]. In der niederländischen Studie war die PM 2.5 -Konzentration selbst nicht mit der Diabetesprävalenz assoziiert, sondern das oxidative Potenzial, was auf die biologische Bedeutung einzelner Komponenten im Feinstaubgemisch hinweist.…”
Section: Inzidenz Des Typ 2-diabetesunclassified